Conquista y pérdida de Yucatán: la arqueología estadounidense en el área maya y el Estado nacional mexicano, 1875-1940. Libro de Guillermo Palacios - Escalona Victoria, José Luis (El Colegio de México, 2023)
Guillermo Palacios’s book, Conquista y pérdida de Yucatán, approaches us to a period of the modern history of Chichén Itzá, between the last decades of the 19th century and the beginning of the 20th century. Besides, in the exploration of the archaeological site the stories of the emergence of American archaeology, the formation of the "Mayan area", the reformulation of state regulations over the past and the nation’s goods, and the history of tourism interweave each other.